2010
DOI: 10.1007/s11096-010-9399-4
|View full text |Cite
|
Sign up to set email alerts
|

A randomized cross-over study to evaluate the swallow-enhancing and taste-masking properties of a novel coating for oral tablets

Abstract: The study showed that MedCoat made tablets easier to swallow for people with difficulties swallowing tablets and that it masked the taste of bitter tasting tablets. MedCoat could therefore be a valuable tool to aid the oral taking of tablets for patients who have difficulties swallowing tablets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 4 publications
(4 reference statements)
0
22
0
Order By: Relevance
“…Uloza et al . investigated the effects of tablet coating on swallowing performance in healthy volunteers . The authors showed that a surface coating enabled the subjects to swallow easily, although evaluation was based only on the subjects' comparative opinions.…”
Section: Discussionmentioning
confidence: 99%
“…Uloza et al . investigated the effects of tablet coating on swallowing performance in healthy volunteers . The authors showed that a surface coating enabled the subjects to swallow easily, although evaluation was based only on the subjects' comparative opinions.…”
Section: Discussionmentioning
confidence: 99%
“…Several technologies have been developed to aid the swallowing of solid oral dosage forms. A disposable device called MedCoat ® (Med Coat AB, Stockholm, Sweden) can be used by the patient to apply a thin coat on the tablet before swallowing [ 71 ]. The coating contains gelatine, sweeteners and flavouring agents and can improve the taste of the tablet.…”
Section: Factors Affecting Acceptability Of Tablets and Capsulesmentioning
confidence: 99%
“…The coating contains gelatine, sweeteners and flavouring agents and can improve the taste of the tablet. In a clinical trial (average age 30 years), the coating improved the ease of swallowing of tablets, especially bitter-flavoured placebo tablets [ 71 ]. A similar flavoured spray product Pill Glide ® (FLAVORx Inc., Columbia, MD, USA) requires the patient to apply the spray to the back of the mouth and tongue before taking tablets or capsules [ 72 ].…”
Section: Factors Affecting Acceptability Of Tablets and Capsulesmentioning
confidence: 99%
“…26 A device that applies a thin coating around the pill, giving a smoother and more slippery feel and masking the taste of medications, has been tested. 27 Forty out of 41 healthy participants with pill-swallowing difficulties reported improved pill swallowing using these pill coating devices, with 54% of them finding it “much easier” to swallow whole tablets. 27 The ingredients used in the medicine coatings are mainly from food sources, and the unpublished pharmacological evaluations have generally regarded them as safe in terms of interacting with medications.…”
Section: Methodsmentioning
confidence: 99%
“… 27 The ingredients used in the medicine coatings are mainly from food sources, and the unpublished pharmacological evaluations have generally regarded them as safe in terms of interacting with medications. 27 …”
Section: Methodsmentioning
confidence: 99%